Needs Analysis in Developing a Multiple Representation Inquiry-Based Learning Module for Promoting Conceptual Change in Basic Physics - Lizelwati, Novia Lizelwati; Mustapa, Izan Roshawaty binti Mustapa; Halim, Anis Diyana binti Halim (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
Understanding waves and optics presents significant challenges for college students, often leading to misconceptions. To address these challenges, it is crucial to implement a learning approach that actively engages students in idea discovery, supported by resources that simplify learning. This study assesses the need for a multi-representation inquiry-based learning module to improve students' understanding of waves and optics. The research was conducted with undergraduate students enrolled in basic physics courses during the 2023/2024 academic year at UIN Mahmud Yunus Batusangkar, involving two classes. Data was collected via a questionnaire distributed through Google Forms. The findings revealed that students face difficulties with mathematical representations and graph analysis. Most students prefer learning through visual aids, such as images and videos, and favor materials, like videos and modules. They also needed real-life examples and video tutorials for problem-solving and concept explanations. The study finds that a learning module that combines visual, mathematical, and real-life examples is important for improving students' understanding and problem-solving abilities in waves and optics.